Three-dimensional elastic-plastic pulse response and energy absorption of curved composite sandwich panel using DQ – Newmark method. (15th June 2019) - Ahmadi, Seyed Ali; Pashaei, Mohammad-Hadi; Jafari-Talookolaei, Ramazan-Ali
Highlights: A nonlinear high-order theory is applied to model compressible core layer. Introducing a new numerical approach, combination of DQ–Newmark method. The programming code requires 50 percent less time than finite element solution. Failure resistance of sandwich panel increases with increasing core density. In the case of H100 core, the panel has most energy absorption. Abstract: The current study aims to present a three-dimensional numerical analysis to predict the elastic-plastic behavior of a single-curvature, simply supported, composite sandwich panel. The PVC foam core is modeled with isotropic elastic-perfectly plastic properties based on the extended non-linear higher-order sandwich panel theory. An efficient and accurate numerical approach, a combination of differential quadrature, and Newmark methods were implemented to distinguish panel layers' deformations and stresses. The non-linear governing partial differential equations of motion are discretized and reduced to ordinary differential equations by applying the differential quadrature method (DQM) and are solved using the Newmark method. The various failure modes of the sandwich panel, including facesheet fracture, foam shear fracture, and foam yield were investigated. The stress components and transient responses obtained from the present method are compared with the finite element solutions using commercial software ANSYS and also compare with those reported in the literature and good agreement is achieved. It is observed that significantly less computational time and hardware capacity for the proposed method is required with respect to the finite element solution. A parametric study proved that sandwich panel with H100 foam core has the highest energy absorption and this parameter increases with increasing the span of the panel.